Corporate taxpayers’ audit experience: Moving forward - Isa, Khadijah; Pope, Jeff; Zainal Abidin, Nor Hafizah (2013)
Tax audits programme (TAP) has become the main function of the Inland Revenue Board Malaysia (IRBM) under a self-assessment system (SAS). The main objective of the TAP is to enhance voluntary compliance by ensuring that taxpayers comply with the provisions of the current tax laws and regulations. Therefore, the implementation of an effective TAP is an important factor in improving the level of tax compliance in a SAS environment. The main objective of this paper is to elicit Malaysian corporate taxpayer’s experience of tax audits. A mixed-mode survey out to examine their attitudes towards audit experience using three components: audit process, audit perception and tax auditors’ professional proficiency. Results suggest that corporate taxpayers had moderate attitudes towards their tax audit experience and perceived that tax auditors had a pre-conceived idea that taxpayers were non-compliant. Although tax auditors had sound communication skills, respondents perceived that tax auditors lacked the ability to handle critical business knowledge and complex issues. Findings from the survey, which provide some feedback from taxpayers who had experienced audits, potentially provide useful information on the effective of the TAP conducted by the IRBM. This paper extends the scope of tax compliance research to corporate taxpayers, and builds upon the limited international and Malaysian literature on TAP. In a tax policy context, this paper enables international tax authorities in general, and Malaysian tax authorities in particular, to have greater confidence in developing and administering the TAP to maintain and/or increase the overall level of corporate compliance.